TRAINING MANAGEMENT OF MUKENA HOME INDUSTRY TO IMPROVE COMMUNITY’S ECONOMIC EMPOWERMENT - Umi Intadiyah; Sri Nurhayati; Nandang Rukanda (IKIP Siliwangi Bandung, 2021)
This research aims to describe Mukena home industry training management ranging from planning, implementation, and results. As well as what are the supporting and inhibiting factors of home industry training itself. This research uses a qualitative approach. Data is collected with participant observation techniques, in-depth interviews, and documentation. The data is analyzed using data collection techniques, data reduction, and data display. These techniques are used to search for data in community empowerment research through mukena Fathiya's home industry training activities in increasing family economic income. The study results include 1) Planning, which includes schedule determination, tutor determination, place and time determination, participant recruitment, training, and practice materials, as well as materials for practice, and sewing tools. 2) Implementation includes: Participant participation, local community participation, and practice directly after they understand the theory. 3) Training results include knowledge, skills, and also increased income. 4) Inhibition factors includes time and cost, training methods, and techniques. The supporting factors include facilities, trainers/tutors, trainees, and practice materials